Moisture-absorbing film laminate and method for producing same
The hygroscopic film is prepared by using a specific photocurable resin composition through the photocuring method, which solves the problem of long-term and insufficient wear resistance in the prior art, and achieves rapid curing and efficient anti-fog performance, while improving the wear resistance of the film.
Patent Information
- Application Number
- CN202411346522.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-09-29
- Filing Date
- 2024-09-26
- Publication Date
- 2025-04-01
AI Technical Summary
The existing hygroscopic films require high temperature and long-term time during the thermal curing process, resulting in low productivity and insufficient wear resistance, which makes it easy to reduce water absorption when improving wear resistance.
A hygroscopic film was prepared by photocuring, and a photocurable resin composition with a (meth)acryloyl group and a photocurable resin composition of three (meth)acrylic monomers and a photoinitiator were used to achieve rapid curing by ultraviolet light curing, and by optimizing the proportion and structure of the composition, the effect of both excellent hygroscopicity and wear resistance was achieved.
The rapid photocuring of the hygroscopic film is achieved, which improves productivity and improves the wear resistance of the film while maintaining excellent hygroscopicity and anti-fog performance.
Smart Images

Figure BDA0005061123520000021 
Figure BDA0005061123520000022 
Figure BDA0005061123520000031
Abstract
Description
Technical Field
[0001] The present invention relates to a hygroscopic film laminate, and to a laminate comprising a substrate and a cured coating of an active energy ray-curable composition having excellent adhesion to the substrate and capable of imparting excellent scratch resistance and hygroscopicity on at least one side of the substrate. Background Art
[0002] In recent years, in vehicles such as cars, trucks, buses and trains, anti-fogging technology that prevents condensation on components such as windows is required from the perspective of energy saving. In the anti-fogging technology, a hygroscopic film is formed on components such as windows, and the moisture that is about to condense is absorbed in the hygroscopic film, thereby exerting an anti-fogging function.
[0003] As such a hygroscopic film, for example, a coating composition composed of a (meth)acrylic resin, a polyol compound and a polyfunctional isocyanate compound (Patent Document 1), a composition containing a polyvinyl acetal resin (Patent Documents 2, 3), and a composition composed of a copolymer, a polyfunctional blocked isocyanate compound and a surfactant (Patent Document 4) have been proposed.
[0004] Prior art literature
[0005] Patent Literature
[0006] Patent Document 1: Japanese Patent Application Publication No. 2019-94468
[0007] Patent Document 2: Japanese Patent Application Publication No. 2012-117025
[0008] Patent Document 3: Japanese Patent Application Publication No. 2001-146585
[0009] Patent Document 4: Japanese Patent Application Publication No. 2016-169288 Summary of the invention
[0010] However, in the existing patent documents, the curing in the heat curing requires high temperature and time, so the productivity is poor and the wear resistance is also insufficient. If the wear resistance is to be improved, there is a method of adding fillers, but the water absorption decreases.
[0011] In view of the above circumstances, an object of the present invention is to provide a moisture-absorbing film laminate having both excellent anti-fogging properties and abrasion resistance, which can be cured in a shorter time than by heat curing and by photocuring using ultraviolet rays.
[0012] The present inventors have conducted intensive studies to achieve the above-mentioned object and, as a result, have found that the above-mentioned problems can be solved by the following means different from those in the prior art documents, thereby completing the present invention.
[0013] That is, the present invention relates to a hygroscopic film laminate, which is a laminate having a substrate and a hygroscopic film formed on a part of the surface of at least one side of the substrate, characterized in that the hygroscopic film is formed by curing a photocurable resin composition, the photocurable resin composition containing: a siloxane resin (A) having a (meth)acryloyl group and three types of the following (meth)acrylic monomers (B), (C) and (D) and a photoinitiator as essential components, the mixing ratio of (A): (B): (C): (D) being 0.1 to 5: 35 to 55: 0.5 to 10: 40 to 60 expressed by weight ratio, the siloxane resin (A) containing a polyorganosilsesquioxane represented by the general formula (1) and having a cage structure in the structural unit as a main component,
[0014] [RS 3 / 2 ] n (1)
[0015] Wherein, R is an organic functional group having a (meth)acryloyl group, n is 8, 10 or 12,
[0016] The (meth)acrylic monomer (B) is a difunctional monomer represented by the general formula (2),
[0017]
[0018] (wherein X is H or methyl, a=1 to 5)
[0019] The (meth)acrylic monomer (C) is a monofunctional monomer represented by the general formula (3),
[0020]
[0021] (wherein X is H or methyl, b=4 to 15)
[0022] The (meth)acrylic monomer (D) is a monofunctional monomer represented by the general formula (4),
[0023]
[0024] (wherein X is H or methyl)
[0025] The water absorption rate of the hygroscopic film is 10% or more and 30% or less, and the haze change value ΔH of the hygroscopic film before and after a Taber abrasion test is 4 or less.
[0026] According to the present invention, it is possible to provide an anti-fog laminate having a moisture absorbing film having both excellent moisture absorbing property and abrasion resistance. DETAILED DESCRIPTION
[0027] Hereinafter, each element constituting the present invention will be described in detail, and the present invention is not limited to the contents described therein as long as it does not exceed the gist thereof. It should be noted that in this specification, when the expression "(meth)acrylic acid" is used, it means one or both of "acrylic acid" and "methacrylic acid". The same applies to "(meth)acrylate" and "(meth)acryloyl".
[0028] [Laminated body]
[0029] The hygroscopic film laminate of the present invention comprises a substrate and a hygroscopic film formed on at least a portion of the surface of the substrate. The hygroscopic film may be formed on a portion of the surface of the substrate, may be formed on one side of the substrate, or may be formed on the entire surface of the substrate.
[0030] As far as the substrate is concerned, as long as a hygroscopic film can be formed, it is not particularly limited, for example, it can be composed of an inorganic material, or it can be composed of an organic material, or a composite material of an inorganic material and an organic material. Among them, glass with poor hygroscopicity is preferred, for example, silicate glass (silicate glass, alkali silicate glass, lead alkali glass (lead alkali glass), soda-lime glass, potassium-lime glass, barium glass), borosilicate glass, phosphate glass, etc., can be listed, and flat glass formed by these glasses (for example, general flat glass (ordinary flat glass, embossed glass (molded plate glass), polished flat glass (grinded plate glass), float glass), composite glass, laminated glass, tempered glass, etc.) can be listed. They can be colorless or colored, and are particularly preferably curved laminated glass used as a vehicle window.
[0031] The siloxane resin (A) having a (meth)acryloyl group contains as a main component a polyorganosilsesquioxane represented by the general formula (1) and having a cage structure in a structural unit (also referred to as a cage polyorganosilsesquioxane. Polyorganosilsesquioxane is also referred to as silsesquioxane).
[0032] In the general formula (1), R is an organic functional group having a (meth)acryloyl group, and n is 8, 10 or 12. Examples of the organic functional group R having a (meth)acryloyl group include groups represented by the following general formula (1a). In the formula (1a), m is an integer of 1 to 3, and R 1 A hydrogen atom or a methyl group.
[0033] CH2=CR 1 -COO-(CH2) m -(1a)
[0034] The silicone resin (A) has an organic functional group R having a (meth)acryloyl group bonded to a silicon atom in a molecule.
[0035] Specific structures of the cage polyorganosilsesquioxane in which n in the general formula (1) is 8, 10, or 12 include cage structures represented by the following structural formulas (5), (6), and (7). In the following formulas, R has the same meaning as R in the general formula (1).
[0036]
[0037]
[0038] The siloxane resin (A) can be produced by the method described in Japanese Patent Application Laid-Open No. 2004-143449, etc. For example, the siloxane resin (A) can be produced by subjecting a silicon compound represented by RSiX3 to a hydrolysis reaction in the presence of a polar solvent and an alkaline catalyst, while partially condensing the resulting hydrolyzate, and further condensing the resulting hydrolyzate in the presence of a non-polar solvent and an alkaline catalyst.
[0039] In the silicon compound RSiX3 used as a raw material, R is an organic functional group having a (meth)acryloyl group, specifically, a group represented by the above-mentioned general formula (1a), and X3 represents a hydrolyzable group.
[0040] If the specific example of preferable R is shown, 3-methacryloyloxypropyl group, methacryloyloxymethyl group, and 3-acryloyloxypropyl group can be illustrated.
[0041] The hydrolyzable group X3 is not particularly limited as long as it is a hydrolyzable group, and examples thereof include alkoxy groups, acetoxy groups, and preferably alkoxy groups. Examples of alkoxy groups include methoxy groups, ethoxy groups, n- or iso-propoxy groups, or n-, iso- or tert-butoxy groups. Methoxy groups are preferred because they are highly reactive.
[0042] Among the silicon compounds represented by RSiX3, if preferred compounds are exemplified, methacryloxymethyltriethoxysilane, methacryloxymethyltrimethoxysilane, 3-methacryloxypropyltrichlorosilane, 3-methacryloxypropyltrimethoxysilane, 3-methacryloxypropyltriethoxysilane, 3-acryloxypropyltrimethoxysilane, and 3-acryloxypropyltrichlorosilane can be cited. Among them, 3-methacryloxypropyltrimethoxysilane, which is easy to obtain as a raw material, is preferably used.
[0043] As the basic catalyst used for the hydrolysis reaction, alkali metal hydroxides such as potassium hydroxide, sodium hydroxide, and cesium hydroxide, or ammonium hydroxide salts such as tetramethylammonium hydroxide, tetraethylammonium hydroxide, tetrabutylammonium hydroxide, benzyltrimethylammonium hydroxide, and benzyltriethylammonium hydroxide can be exemplified. Among these, tetramethylammonium hydroxide is preferably used from the aspect of high catalyst activity. The basic catalyst is usually used as an aqueous solution.
[0044] Regarding the hydrolysis reaction conditions, the reaction temperature is preferably 0 to 60°C, more preferably 20 to 40°C. If the reaction temperature is lower than 0°C, the reaction rate slows down, and the hydrolyzable groups remain in an unreacted state, resulting in a large amount of reaction time. On the other hand, if it is higher than 60°C, since the reaction rate is too fast, a complex condensation reaction proceeds, and as a result, the high molecular weight of the hydrolyzate is promoted. In addition, the reaction time is preferably more than 2 hours. If the reaction time is less than 2 hours, the hydrolysis reaction does not proceed sufficiently, and the hydrolyzable groups may remain in an unreacted state.
[0045] The hydrolysis reaction requires the presence of water, but it can be supplied by an aqueous solution of an alkaline catalyst or added as additional water. The amount of water can be an amount sufficient to hydrolyze the hydrolyzable group, preferably 1.0 to 1.5 times the theoretical amount. In addition, an organic polar solvent is required for hydrolysis. As the organic polar solvent, alcohols such as methanol, ethanol, 2-propanol, or other organic polar solvents can be used. It is preferably a lower alcohol having 1 to 6 carbon atoms that is soluble in water, and 2-propanol is more preferably used. If a non-polar solvent is used, the reaction system does not become uniform, the hydrolysis reaction does not proceed sufficiently, and unreacted hydrolyzable groups remain, which is not preferred.
[0046] After the hydrolysis reaction is completed, water or a reaction solvent containing water is separated. Water or a reaction solvent containing water can be separated by means such as reduced pressure evaporation. In order to fully remove moisture and other impurities, a non-polar solvent can be added to dissolve the hydrolysis reaction product, the solution can be washed with saline solution, and then dried with a desiccant such as anhydrous magnesium sulfate. If the non-polar solvent is separated by means such as evaporation, the hydrolysis reaction product can be recovered, and if the non-polar solvent can be used as a non-polar solvent used in the next reaction, it is not necessary to separate it.
[0047] In the hydrolysis reaction, a condensation reaction of the hydrolyzate occurs together with the hydrolysis. As for the hydrolysis product accompanying the condensation reaction of the hydrolyzate, it usually becomes a colorless viscous liquid with a number average molecular weight of 1400 to 5000. The hydrolysis product varies depending on the reaction conditions. Preferably, it becomes an oligomer with a number average molecular weight of 1400 to 3000, and most of the hydrolyzable groups X, preferably almost all, are substituted with OH groups, and then most of the OH groups, preferably more than 95%, are condensed. The structure of the hydrolysis product is a variety of cage-type, ladder-type, and random silsesquioxanes. For compounds with cage structures, the proportion of complete cage structures is small, and the incomplete cage structure with a part of the cage open is the main one. Therefore, by further heating the hydrolysis product obtained in the hydrolysis in the presence of an alkaline catalyst in an organic solvent, the siloxane bonds are condensed (called re-condensation), thereby selectively producing cage-type silsesquioxanes.
[0048] Specifically, it is carried out as described below. That is, as described above, after the hydrolysis reaction is completed, water or a reaction solvent containing water is separated, and then a re-condensation reaction is carried out in the presence of a non-polar solvent and an alkaline catalyst. For the reaction conditions of the re-condensation reaction, the reaction temperature is preferably in the range of 100 to 200°C, and more preferably 110 to 140°C. In addition, if the reaction temperature is too low, a driving force sufficient for the re-condensation reaction cannot be obtained, and the reaction cannot proceed. If the reaction temperature is too high, the (meth)acryloyl group may cause a self-polymerization reaction, so it is necessary to control the reaction temperature, or add an inhibitor, etc. The reaction time is preferably 2 to 12 hours. The amount of the non-polar solvent used may be an amount sufficient to dissolve the hydrolysis reaction product, and the amount of the alkaline catalyst used may be in the range of 0.1 to 10wt% relative to the hydrolysis reaction product.
[0049] As the non-polar solvent, any solvent that is insoluble in water or almost insoluble in water may be used, and hydrocarbon solvents are preferred. As the hydrocarbon solvent, there are non-polar solvents with low boiling points such as toluene, benzene, and xylene. Among them, toluene is preferably used. In addition, as the alkaline catalyst, an alkaline catalyst that can be used in the above-mentioned hydrolysis reaction can be used, and examples thereof include alkali metal hydroxides such as potassium hydroxide, sodium hydroxide, and cerium hydroxide, or ammonium hydroxide salts such as tetramethylammonium hydroxide, tetraethylammonium hydroxide, tetrabutylammonium hydroxide, benzyltrimethylammonium hydroxide, and benzyltriethylammonium hydroxide, and catalysts that are soluble in non-polar solvents such as tetraalkylammonium are preferred.
[0050] The hydrolyzate used in the re-condensation preferably uses a product that is washed, dehydrated, and concentrated, and can be used even if it is not washed or dehydrated. During its reaction, water may exist, but it is not necessary to add it actively, and it may stay at the moisture level brought in from the alkaline catalyst solution. It is explained that when the hydrolysis of the hydrolyzate is not fully carried out, although it is necessary to hydrolyze the remaining hydrolyzable groups to a moisture content greater than the theoretical amount required, generally speaking, the hydrolysis reaction is fully carried out. After the re-condensation reaction, the catalyst is washed and removed, concentrated, and a cage-type silsesquioxane mixture having a silicon atom number and a (meth) acryloyl number equal in the molecule is obtained.
[0051] The silsesquioxane mixture thus obtained varies depending on the reaction conditions and the state of the hydrolyzate. It is believed that, in terms of the constituent components, the various cage silsesquioxanes account for more than 70% by weight of the total, and the remainder is ladder-type and randomly cross-linked silsesquioxanes. Since their separation is difficult and requires a lot of effort, in the present invention, it is preferred that the silsesquioxane containing more than 70% by weight of the cage silsesquioxane represented by the general formula (1) is a siloxane resin (A) having a (meth)acryloyl group. In terms of the constituent components of the various cage silsesquioxanes, it is preferred that T8 represented by the general formula (5) is 10 to 40% by weight, T10 represented by the general formula (6) is 30 to 50% by weight, and T12 represented by the general formula (7) is 5 to 20% by weight, and other components of less than 50% by weight may be contained. As for T8, by placing the silsesquioxane mixture at a temperature below 20°C, it can be precipitated and separated as needle-shaped crystals. The content ratio of cage silsesquioxane can be confirmed by using, for example, GPC, LC-MS, or the like.
[0052] The photocurable resin composition of the present invention is obtained by mixing a siloxane resin (A) having a (meth)acryloyl group and (meth)acrylic monomers (B), (C), and (D) at a weight ratio of (A): (B): (C): (D) = 0.1 to 5: 35 to 55: 0.5 to 10: 40 to 60, and adding a photoinitiator. From the perspective of the balance between water absorption and abrasion resistance, a more preferred mixing ratio is (A): (B): (C): (D) = 1 to 5: 40 to 45: 3 to 8: 45 to 55.
[0053] The siloxane resin (A) having a (meth)acryloyl group used in the present invention may be a mixture of cage polyorganosilsesquioxanes T8, T10, and T12, or may be a product obtained by separating or concentrating one or two of T8 and the like therefrom.
[0054] The siloxane resin (A) having a (meth)acryloyl group used in the present invention is not limited to the silicone resin obtained by the above-mentioned production method.
[0055] Siloxane resin (A) is a multifunctional (meth) acrylate compound having the same number of (meth) acryloyl groups as n. By mixing in a certain ratio and performing a three-dimensional crosslinking reaction, it is expected that the wear resistance of the hygroscopic film can be improved. As for the preferred mixing ratio, 0.1 to 5 parts by weight are preferred relative to the photocurable resin composition. If it is less than 0.1 parts by weight, the wear resistance becomes insufficient, and if it is higher than 5 parts by weight, the hygroscopic film becomes a hard and brittle film. The curing shrinkage also becomes larger, so cracks are generated during curing, and the hygroscopic film becomes hard, which is not easy to expand by moisture absorption, and may lead to a decrease in water absorption properties. From the viewpoint of improving wear resistance, 1 to 5 parts by weight are more preferred.
[0056] As for the (meth)acrylic monomer (B) used in the present invention, specifically, it is glycerol 1,3-diglycerol alcohol acid diacrylate and glycerol 1,3-diglycerol alcohol acid dimethacrylate, which are acrylic acid or methacrylic acid adducts of the reaction products of glycerol and epichlorohydrin. The (meth)acrylic monomer (B) has 3 hydroxyl groups and 2 (meth)acryloyl groups in one molecule, so it has high hydrophilicity, improves the water absorption rate of the hygroscopic film, constructs a moderate cross-linking structure, and can be expected to impart wear resistance. In terms of the mixing ratio, 35 to 55 parts by weight are preferred relative to the photocurable resin composition. If it is less than 35 parts by weight, the water absorption characteristics and abrasion resistance become insufficient, and if it is more than 55 parts by weight, the hygroscopic film may become hard and brittle. The more preferred range is 40 to 50 parts by weight.
[0057] The (meth)acrylic monomer (C) used in the present invention is specifically methoxy polyethylene glycol acrylate or methoxy polyethylene glycol methacrylate. b is 4 to 15, and is more preferably 6 to 13 from the perspective of the balance between water absorption and abrasion resistance. The (meth)acrylic monomer (C) is monofunctional and has multiple ether bonds in one molecule, so it can be expected to impart hygroscopic properties and moderate softness to the hygroscopic film. In terms of the mixing ratio, 0.5 to 10 parts by weight is preferred relative to the photocurable resin composition. If it is less than 0.5 parts by weight, the water absorption characteristics become insufficient, and if it is greater than 10 parts by weight, it becomes excessively soft and the wear resistance becomes insufficient. The more preferred mixing ratio is 1 to 8 parts by weight.
[0058] As for the (meth) acrylic monomer (D) used in the present invention, specifically, it is 2-hydroxyethyl methacrylate or 2-hydroxyethyl acrylate. The (meth) acrylic monomer (D) is monofunctional and has one hydroxyl group in one molecule, so it can be expected to improve the hygroscopic properties of the hygroscopic film. In terms of the mixing ratio, 40 to 60 parts by weight are preferred relative to the photocurable resin composition. If it is less than 40 parts by weight, the water absorption characteristics become insufficient, and if it is more than 60 parts by weight, the three-dimensional crosslinking of the hygroscopic film is insufficient, and it is possible to become a soft film and the wear resistance becomes insufficient. The more preferred mixing is 45 to 55 parts by weight.
[0059] In the photocurable resin composition of the present invention, the amount of the photoinitiator added is preferably in the range of 0.01 to 10 parts by weight relative to a total of 100 parts by weight of the resin composition (resin component excluding water and solvent). If it is less than this range, crosslinking becomes insufficient, the elastic modulus decreases, and the expected surface height cannot be obtained. On the contrary, even if it is contained in excess of this range, it is not expected to further increase the reaction rate. More preferably, it is in the range of 5 to 10 parts by weight.
[0060] The photopolymerization initiator is not particularly limited, and a wide range of general-purpose photopolymerization initiators can be used, and preferably, compounds such as acetophenone-based, benzoyl-based, benzophenone-based, thioxanthone-based, and acylphosphine oxide-based compounds can be used. Specifically, trichloroacetophenone, diethoxyacetophenone, 1-phenyl-2-hydroxy-2-methylpropane-1-one, 1-hydroxycyclohexylphenyl ketone, 2-methyl-1-(4-methylthiophenyl)-2-morpholinopropane-1-one, benzoin methyl ether, benzyl dimethyl ketal, benzophenone, 4,4'-bis(diethylamino)-benzophenone, benzophenone-2-carboxylic acid methyl ester, 4-benzoyl-4'-methyldiphenyl sulfide, 2-hydroxy-2-methyl-1-phenylpropane-1 -ketone, 1-[4-(2-hydroxyethoxy)-phenyl]-2-hydroxy-2-methyl-1-propane-1-one, 2-hydroxy-1-{4-[4-(2-hydroxy-2-methylpropionyl)-benzyl]phenyl}-2-methylpropane-1-one, 2-methyl-1-[4-(methylthio)phenyl]-2-morpholinopropane-1-one, thioxanthone, 2,4,6-trimethylbenzoyldiphenylphosphine oxide, methylphenylglyoxylate (salt), camphorquinone, benzil, anthraquinone, Michler's ketone, etc. In addition, a photoinitiator auxiliary agent or a sensitizer that exerts an effect in combination with a photopolymerization initiator can also be used in combination.
[0061] The photocurable resin composition may be diluted with a solvent in order to adjust the solid content concentration, improve dispersion stability, improve coating properties, improve adhesion to a substrate, and the like.
[0062] Examples of the solvent include organic solvents, such as alcohols, ketones, ethers, esters, cellosolves, and aromatic compounds. Specific examples include methanol, ethanol, 1-propanol, 2-propanol, 1-butanol, 2-butanol, isobutyl alcohol, tert-butyl alcohol, benzyl alcohol, 2-methoxyethanol, 2-ethoxyethanol, 2-(methoxymethoxy)ethanol, 2-butoxyethanol, furfuryl alcohol, tetrahydrofurfuryl alcohol, diethylene glycol, diethylene glycol monomethyl ether, diethylene glycol monoethyl ether, diethylene glycol monobutyl ether, 1-methoxy-2-propanol, 1-ethoxy-2-propanol, dipropylene glycol, dipropylene glycol monomethyl ether, dipropylene glycol monoethyl ether, tripropylene glycol monomethyl ether, diacetone alcohol, acetone, methyl ethyl ketone, 2-pentanone, 3-pentanone, 2-hexanone, methyl isobutyl ketone, 2-heptanone, 4-heptanone, diisobutyl ketone, cyclohexanone, methylcyclohexanone, acetophenone, diethyl ether, dipropyl ether, diisopropyl ether, dibutyl ethyl ether, dihexyl ether, anisole, phenethyl ether, tetrahydrofuran, tetrahydropyran, 1,2-dimethoxyethane, 1,2-diethoxyethane, 1,2-dibutoxyethane, diethylene glycol dimethyl ether, diethylene glycol diethyl ether, diethylene glycol dibutyl ether, glycerol ether, methyl acetate, ethyl acetate, propyl acetate, isopropyl acetate, butyl acetate, isobutyl acetate, sec-butyl acetate, amyl acetate, isoamyl acetate, 3-methoxybutyl acetate, 2-ethylbutyl acetate, 2-ethylhexyl acetate, methyl propionate, ethyl propionate, butyl propionate, γ-butyrolactone, 2-methoxyethyl acetate, 2-ethoxyethyl acetate, 2-butoxyethyl acetate, 2-phenoxyethyl acetate, diethylene glycol monoethyl ether acetate, diethylene glycol monobutyl ether acetate, benzene, toluene, xylene. These organic solvents can be used alone or in combination of two or more.
[0063] To the moisture-absorbing film of the present invention, an ultraviolet absorber or a light stabilizer (ultraviolet stabilizer) may be added in order to improve weather resistance.
[0064] As the ultraviolet absorber, inorganic oxide fine particles such as titanium oxide, cerium oxide, zirconium oxide, and zinc oxide, metal chelate compounds of titanium, zinc, zirconium, and the like, and (partial) hydrolyzates and condensates thereof, and organic ultraviolet absorbers can be used.
[0065] As examples of organic systems, preferred main skeletons are hydroxybenzophenone-based, benzotriazole-based, cyanoacrylate-based, and triazine-based compound derivatives. Further examples include polymers containing these ultraviolet absorbers in the side chains, ultraviolet absorbers having reactive functional groups, or silylated ultraviolet absorbers, and (partial) hydrolysis condensates thereof. Specifically, there can be mentioned 2-(2-hydroxy-5-tert-butylphenyl)-2H-benzotriazole, 2-[5-chloro-(2H)-benzotriazol-2-yl]-4-methyl-6-(tert-butyl)phenol, 2-(2H-benzotriazol-2-yl)6-(1-methyl-1-phenylethyl)-4-(1,1,3,3-tetramethylbutyl)phenol, 2-[4-[(2-hydroxy-3-(2'-ethyl)hexyl)oxy]-2-hydroxyphenyl]4,6-bis(2,4-dimethylphenyl)-1,3,5-triazine, (co)polymers of 2-hydroxy-4-(2-acryloyloxyethoxy)benzophenone, (co)polymers of 2-(2'-hydroxy-5'-methacryloyloxyethylphenyl)-2H-benzotriazole, etc. These ultraviolet absorbers can be used in combination of two or more.
[0066] As the ultraviolet stabilizer, a compound having one or more cyclic hindered amine structures in the molecule is preferred. Specifically, bis(2,2,6,6-tetramethyl-1-(octyloxy)-4-piperidinyl) ester, 3-dodecyl-1-(2,2,6,6-tetramethyl-4-piperidinyl)pyrrolidine-2,5-dione, N-methyl-3-dodecyl-1-(2,2,6,6-tetramethyl-4-piperidinyl)pyrrolidine-2,5-dione, N-acetyl-3-dodecyl-1-(2,2,6,6-tetramethyl-4-piperidinyl)pyrrolidine-2,5-dione, The ultraviolet light stabilizers include bis(2,2,6,6-tetramethyl-4-piperidyl)pyrrolidine-2,5-dione, bis(2,2,6,6-tetramethyl-4-piperidyl)sebacate, bis(1,2,2,6,6-pentamethyl-4-piperidyl)sebacate, tetrakis(2,2,6,6-tetramethyl-4-piperidyl), 1,2,3,4-butanetetracarboxylate, tetrakis(1,2,2,6,6-pentamethyl-4-piperidyl), and the like. Two or more of these ultraviolet light stabilizers may be used in combination.
[0067] It should be noted that in the photocurable resin composition of the present invention, in addition to the above-mentioned components, various additives can be added, for example, within the range that does not reduce the function. As various additives, organic / inorganic fillers, plasticizers, flame retardants, heat stabilizers, antioxidants, light stabilizers, ultraviolet absorbers, lubricants, antistatic agents, mold release agents, foaming agents, nucleating agents, colorants, crosslinking agents, dispersing aids, resin components, etc. can be exemplified.
[0068] Examples of methods for forming a hygroscopic film composed of a photocurable resin composition on a substrate include casting, roll coating, rod coating, spray coating, air knife coating, spin coating, flow coating, curtain coating, and dipping. The coating film thickness is adjusted by the solid content concentration in consideration of the film thickness after curing by drying and irradiation with active energy rays.
[0069] When a solvent is used, after coating, the solvent is preferably removed by drying, etc. The drying temperature is preferably a condition that does not deform the substrate to be used, and the drying time is preferably 1 hour or less from the viewpoint of productivity.
[0070] The hygroscopic film of the present invention can be manufactured by curing the above-mentioned photocurable resin composition by irradiating it with active energy rays such as visible light, ultraviolet light, electron beam, etc. Preferably, a cured molded body can be obtained by irradiating ultraviolet light with a wavelength of 10 to 400 nm and visible light with a wavelength of 400 to 700 nm. There is no particular restriction on the wavelength of the light used, and it is particularly preferred to use near-ultraviolet light with a wavelength of 200 to 400 nm. As lamps used as ultraviolet light sources, low-pressure mercury lamps (output: 0.4 to 4 W / cm), high-pressure mercury lamps (40 to 160 W / cm), ultra-high-pressure mercury lamps (173 to 435 W / cm), metal halide lamps (80 to 160 W / cm), etc. can be exemplified.
[0071] The method of obtaining a hygroscopic film by irradiation with active energy rays such as light irradiation may be carried out in an oxygen-blocked atmosphere or in an air atmosphere, preferably in an oxygen-blocked atmosphere. Specifically, there are methods of filling the irradiation space with nitrogen and methods of using a laminated film to block oxygen during irradiation.
[0072] As for the thickness of the hygroscopic film of the present invention, from the viewpoint of scratch resistance and adhesion, the thickness of the hygroscopic film is preferably 1 to 100 μm, and more preferably 3 to 50 μm. When it is thinner than 1 μm, the water absorption of the hygroscopic film is small, and the anti-fogging performance of the vehicle window component disappears in a short time. On the other hand, when it is thicker than 100 μm, the water absorption is large, and the anti-fogging performance can be maintained for a long time, but due to the difference in refractive index with the substrate, visibility is reduced.
[0073] The moisture absorption of the moisture-absorbing film of the moisture-absorbing film laminate of the present invention thus obtained is 10% to 30%, and the haze change value ΔH before and after the Taber abrasion test conducted with a Taber abrasion wheel CS-10F, a load of 500 g, and a rotation number of 100 is 4 or less.
[0074] Example
[0075] Examples of the present invention are shown below. The silicone resin (A) used in the examples was obtained by the method shown in the following synthesis example.
[0076] [Synthesis example 1]
[0077] In a reaction container equipped with a stirrer, a dropping funnel, and a thermometer, 40 ml of 2-propanol (IPA) as a solvent and a 5% tetramethylammonium hydroxide aqueous solution (TMAH aqueous solution) as an alkaline catalyst are placed. 15 ml of IPA and 12.69 g of 3-methacryloxypropyltrimethoxysilane (MTMS: SZ-6300 manufactured by Toray Dawuconing Silicorne Co., Ltd.) are placed in the dropping funnel, and while stirring the reaction container, the IPA solution of MTMS is added dropwise at room temperature for 30 minutes. After the addition of MTMS is completed, it is stirred for 2 hours without heating. After stirring for 2 hours, the solvent is removed under reduced pressure and dissolved with 50 ml of toluene. The reaction solution is washed with saturated brine until it becomes neutral, and then dehydrated with anhydrous magnesium sulfate. The anhydrous magnesium sulfate is filtered and separated, and concentrated to obtain 25.8 g of a hydrolysis product (silsesquioxane). The silsesquioxane is a colorless viscous liquid soluble in various organic solvents.
[0078] Secondly, 20.65 g of the above-obtained silsesquioxane, 82 ml of toluene and 3.0 g of a 10% TMAH aqueous solution were placed in a reaction vessel equipped with a stirrer, a Dean-Stark, and a condenser, and the mixture was slowly heated to distill off the water. Furthermore, the mixture was heated to 130°C and the toluene was subjected to a re-condensation reaction at the reflux temperature. The temperature of the reaction solution at this time was 108°C. After the toluene was refluxed and stirred for 2 hours, the reaction was stopped. The reaction solution was washed with saturated brine until it became neutral, and then dehydrated with anhydrous magnesium sulfate. The anhydrous magnesium sulfate was filtered and separated, and concentrated to obtain 18.77 g of the target cage-type silsesquioxane (mixture). The obtained cage-type silsesquioxane (S1) was a colorless viscous liquid soluble in various organic solvents.
[0079] The mass analysis after liquid chromatography separation of the reaction product after the re-condensation reaction confirmed that the molecular ions with ammonium ions in the molecular structures of the above-mentioned structural formulas (5), (6) and (7) in which R is a methacryloyl group were found to have a composition ratio of T8:T10:T12:others of about 2:4:1:3, and it was confirmed that the silicone resin was a component mainly composed of a cage-type structure. It should be noted that T8, T10 and T12 correspond to the compounds in which R is a methacryloyl group in the formulas (5), (6) and (7), respectively.
[0080] [Example 1]
[0081] As the component (A), A1: a cage-type silicone resin having methacryloyl groups on all silicon atoms obtained in Synthesis Example 1,
[0082] As the component (B), B1: an acrylic acid adduct of a reaction product of glycerin and epichlorohydrin (Epoxis Ester 80MFA manufactured by Kyoeisha Chemical Co., Ltd.),
[0083]
[0084] As the component (C), C1: methoxy polyethylene glycol acrylate (n=average 13, AM-130G manufactured by Shin-Nakamura Chemical Co., Ltd.),
[0085]
[0086] As the component (D), D1: 2-hydroxyethyl methacrylate,
[0087]
[0088] A1, B1, C1, and D1 were prepared at 3, 50, 2, and 45 parts by weight, respectively; P1 as a photopolymerization initiator: 7.5 parts by weight of 1-hydroxycyclohexyl phenyl ketone (Omnirad184 manufactured by IGM); P2: 0.75 parts by weight of 2-methyl-1-[4-(methylthio)phenyl]-2-morpholinopropane-1-one (Omnirad907 manufactured by IGM); and S1 as a solvent: propylene glycol monomethyl ether. 80 parts by weight of ether, 2.5 parts by weight of 2-[5-chloro-(2H)-benzotriazol-2-yl]-4-methyl-6-(tert-butyl)phenol (TINUVIN384-2 manufactured by BASF) as an ultraviolet absorber U1, 0.5 parts by weight of di(1,2,2,6,6-pentamethyl-4-piperidinyl)sebacate (TINUVIN292 manufactured by BASF) as a light stabilizer U2, and 0.5 parts by weight of a fluorine-based surface conditioner F1 were mixed to obtain a photocurable resin composition.
[0089] Next, the silane coupling agent-treated glass plate was coated with a spin coater so that the film thickness after drying was 15 μm, and dried at 60° C. for 10 minutes. Then, the silane coupling agent was placed in a nitrogen atmosphere and the cumulative exposure was 4000 mJ / cm 2 Use curing 500mW / cm 2 The resulting mixture was cured using a metal halide lamp to obtain a hygroscopic film laminate having a 15 μm thick hygroscopic film formed on the surface of the glass substrate.
[0090] [Examples 2 to 9, Comparative Examples 1 to 8]
[0091] A hygroscopic film laminate was obtained in the same manner as in Example 1 except that the raw materials, blending ratio and film thickness described in Table 1 were used. In addition, other abbreviations in the table are as follows.
[0092] C2: Methoxy polyethylene glycol acrylate (n=average 9, M-90G manufactured by Shin-Nakamura Chemical Co., Ltd.)
[0093]
[0094] C3: Methoxytetraglycol methacrylate (n=4, M-40G manufactured by Shin-Nakamura Chemical Co., Ltd.)
[0095]
[0096] Z1: methoxy polyethylene glycol acrylate (n = average 23, Shin-Nakamura Chemical Co., Ltd. M-230G)
[0097]
[0098] Z2: Glyceryl dimethacrylate (Lite Ester G-101P manufactured by Kyoeisha Chemical Co., Ltd.)
[0099]
[0100] Z3: 2-Hydroxypropyl Methacrylate
[0101]
[0102] The evaluation results are shown in Table 1.
[0103] [Hygroscopicity (anti-fogging)]
[0104] The water absorption of the hygroscopic film in each laminate was measured by the following method: In a 20% RH environment, the weight of a glass substrate having a hygroscopic film (hereinafter referred to as a sample) was measured with a balance, and the weight of the hygroscopic film was calculated from the previously measured weight of the glass substrate alone.
[0105] After the sample was kept in a constant temperature and humidity environment of 95% RH (set temperature: 30° C.) for 1 to 2 hours, the weight change of the sample was measured with a balance and regarded as the water absorption of the hygroscopic film.
[0106] The water absorption rate was calculated from the weight of the hygroscopic film and the amount of water absorbed by the hygroscopic film based on the following formula.
[0107] Water absorption rate (%) = (water absorption of hygroscopic film / weight of hygroscopic film) × 100
[0108] The higher the water absorption rate, the better the hygroscopicity. The hygroscopicity was evaluated based on the water absorption rate using the following criteria.
[0109] ○: Water absorption ≥ 10%
[0110] ×: Water absorption rate <10%
[0111] [Taber wear resistance (scratch resistance)]
[0112] The test was performed using a wear wheel CS-10F in the Taber wear test in accordance with JIS K7204 at a load of 500 g and 100 rotations, and the Taber wear resistance was evaluated based on the haze values before and after the test.
[0113] ΔH = (haze after Taber abrasion test) - (haze before test)
[0114] The smaller ΔH (%) is, the better the wear resistance is, and the evaluation was conducted based on the following criteria.
[0115] ○: 0<ΔH≤4
[0116] ×: ΔH>4
[0117] [Comprehensive evaluation]
[0118] The evaluation results of hygroscopicity (anti-fogging property) and Taber abrasion resistance (scratch resistance) were comprehensively evaluated.
[0119] ○: The evaluation results of hygroscopicity and abrasion resistance were both good (○).
[0120] ×: At least one of the evaluation results of hygroscopicity and abrasion resistance is poor (×).
[0121]
Claims
1. A hygroscopic film laminate comprising a substrate and a hygroscopic film formed on a surface of at least one side of the substrate, characterized in that: The hygroscopic film is formed by curing a photocurable resin composition, wherein the photocurable resin composition contains a siloxane resin (A) having a (meth)acryloyl group, three types of the following (meth)acrylic monomers (B), (C) and (D), and a photoinitiator as essential components, wherein the mixing ratio of (A): (B): (C): (D) is 0.1 to 5: 35 to 55: 0.5 to 10: 40 to 60, expressed as a weight ratio. The siloxane resin (A) contains as a main component a polyorganosilsesquioxane represented by the general formula (1) and having a cage structure in its structural unit. [RSiO 3 / 2 ] n (1) Wherein, R is an organic functional group having a (meth)acryloyl group, n is 8, 10 or 12, The (meth)acrylic monomer (B) is a difunctional monomer represented by the general formula (2), Wherein, X is H or methyl, a=1 to 5, The (meth)acrylic monomer (C) is a monofunctional monomer represented by the general formula (3), Wherein, X is H or methyl, b=4 to 15, The (meth)acrylic monomer (D) is a monofunctional monomer represented by the general formula (4), Wherein, X is H or methyl, The water absorption rate of the hygroscopic film is 10% or more and 30% or less, and the haze change value ΔH of the hygroscopic film before and after the Taber abrasion test is 4 or less.
2. The hygroscopic film laminate according to claim 1, wherein The hygroscopic film contains an ultraviolet absorber and / or a light stabilizer. The moisture-absorbing film laminate according to claim 1 , which is used as a window member for a vehicle.
4. A method for producing a hygroscopic film laminate, which is a method for producing the hygroscopic film laminate according to claim 1, characterized in that: include: The photocurable composition is applied to a substrate, and the applied photocurable composition is irradiated with active energy rays, thereby curing the photocurable composition to form a moisture absorbing film.
5. The method for producing a hygroscopic film laminate according to claim 4, wherein: In the step of curing the photocurable composition to form a hygroscopic film, the irradiation conditions of the active energy ray are: light with a wavelength range of 200 nm to 400 nm, and an illuminance of 200 to 900 mW / cm 2 The accumulated light intensity is 1000~8000mJ / cm 2 .
Citation Information
Patent Citations
Antifogging substrate and forming method therefor
JP2001146585A
Cage-type silsesquioxan resin with functional group and method for producing the same
JP2004143449A
Anti-fog coated article
JP2012117025A
Antifogging agent composition and antifogging article using the same
JP2016169288A
Coating composition, cured film, and article having the cured film
JP2019094468A